Internalisasi Nilai Keagamaan Anak dalam Perspektif Surah Luqman Ayat 13–19 dan Hadis Fitrah: Sebuah Kajian Integratif - Kiki Wiyandi; Larasati; Pathur Rahman; Mukmin (WISE Pendidikan Indonesia, 2026)
The internalization of religious values in children is the main foundation for forming Muslim character from an early age. This study aims to analyze the concept of internalization of religious values in children based on Surah Luqman verses 13-19 and the hadith about the fitrah (innate nature) of children (HR. al-Bukhari No. 1358 & HR. Muslim No. 2658), as well as to formulate an implementation model in the context of empowering the educational community. The method used is library research with a thematic interpretation approach (maudhu’i) and hadith analysis (tahlili). The results show that the religious values in Surah Luqman verses 13-19 include monotheism (tauhid), devotion to parents (birrul walidain), awareness of Allah's supervision, prayer (shalat), enjoining good and forbidding evil (amar ma’ruf nahi munkar), patience, and noble character. The hadith of fitrah affirms that children are born in a pure state with the potential for monotheism, and parents act as the main actors in directing that fitrah. The integration of both produces a gradual internalization model based on affection, role modeling, and habituation from an early age. The implications of this study emphasize the importance of the role of parents and educators as agents of empowerment of the educational community in instilling religious values in children.